RELATIONSHIP OF USE OF YOUTH INFORMATION AND COUNSELING CENTER (PIK-R) SERVICES ON ADOLESCENT REPRODUCTIVE HEALTH BEHAVIOR AT SMAN 2 GOWA - Surahmawati Surahmawati; Andi Azizah Abdillah Faisal (Homes Journal = Hospital Management Studies Journal, 2023)
PIK-R (Adolescent Information and Counseling Center) is a forum for PKBR program activities that can be used to assist youth in solving problems they face by providing information, counseling, and education related to reproductive health. By using PIK-R students can avoid the risk of TRIAD KRR. This study aims to determine the relationship between the use of the Information and Counseling Center for Adolescents (PIK-R) on adolescent reproductive health behavior at SMAN 2 Gowa. The type of research used is quantitative with an observational analytic approach and uses a cross-sectional design. Based on the results of the bivariate test, showed that there was no relationship between consultation (p = 0.102) on adolescent reproductive health behavior. However, there was a relationship between socialization (p = 0.010), parental support (p = 0.000), and social environment (p = 0.000) on adolescent reproductive health behavior. Recommendations for schools and PIK-R administrators to maximize the use of PIK-R starting from socialization and consultation. Parents of students are expected to pay more attention, educate and suggest entering organizations that can influence their adolescent reproductive health behavior. It is also expected for students to participate and take advantage of the activities carried out by PIK-R and choose a good social environment.